A composite score based on immune-related gene prognostic index and m6A risk score of head and neck squamous cell carcinoma - Yang, Yizhou; Cai, Zeman; Huang, Kaichun; Li, Mei; Wang, Xiao; Lin, Yinbing; Chen, Sijie; Yang, Zhining; Lin, Zhixiong (Frontiers in Genetics, 2023)
Background: Immunotherapy has been demonstrated favorable in head and neck squamous cell carcinoma (HNSCC). Studies indicated that immune-related gene prognostic index (IRGPI) was a robust signature, and N6-methyladenosine (m6A) methylation had a significant impact on the tumor immune microenvironment (TIME) and immunotherapy of HNSCC. Thus, combining IRGPI with m6A status should offer a better predictive power for immune responses. Methods: HNSCC samples from The Cancer Genome Atlas (TCGA, n=498) and Gene Expression Omnibus database (GSE65858, n = 270) were used in this study. Cox regression analysis was used to construct the IRGPI through immune-related hub genes which were identified by weighted gene co-expression network analysis (WGCNA). The m6A risk score was constructed by least absolute shrinkage and selection operator regression analysis. Principal component analysis was used to construct a composite score, and systematically correlate subgroups according to TIME cell-infiltrating characteristics. Results: A composite score was determined based on IRGPI and m6A risk score. HNSCC patients in the TCGA were divided into four subgroups：A (IRGPI-High&m6A-risk-High, n=127), B (IRGPI-High&m6A-risk-Low, n=99), C (IRGPI-Low&m6A-risk-High, n=99) and D (IRGPI-Low&m6A-risk-Low, n=128), and overall survival (OS) was significantly different between subgroups (P < 0.001). The characteristics of TIME cell infiltration in the four subgroups were significantly different in subgroups (P < 0.05). The ROC curves show the predictive value of composite score for OS was superior to any other scores. Conclusions: The composite score is a promising prognostic signature which might distinguish immune and molecular characteristics, predict prognosis, and guide more effective immunotherapeutic strategies for HNSCC.